Optimizing Non-Cash Food Assistance Programs through Analysis of Supporting Factors and Obstacles: Optimalisasi Program Bantuan Pangan Non Tunai melalui Analisis Faktor Pendukung dan Hambatan - Maydi Reichies Manurun; H. M. Z Arifin; Trisna Waty Riza Eryani; Ahmad Yani (Academia Open, 2025)
General Background: The Non-Cash Food Assistance Program (BPNT) is a strategic government instrument aimed at improving the welfare of underprivileged communities through non-cash food assistance. Specific Background: In Jahab Subdistrict, BPNT implementation benefits from strong community participation and strategically located e-Warong outlets; however, it still faces challenges such as limited human resources, insufficient guidance for Beneficiary Families (KPM), and uncertainty in disbursement schedules. Knowledge Gap: Previous studies rarely evaluate the alignment between BPNT’s objectives and its outcomes at the subdistrict level, nor do they provide a detailed identification of supporting and inhibiting factors. Aims: This study aims to evaluate BPNT implementation in Jahab, assess the alignment between program objectives and results, and identify supporting and inhibiting factors to improve implementation. Results: Findings reveal that program success is supported by community participation, strategic e-Warong locations, and adequate accessibility, but hindered by limited human resources, minimal guidance, inaccurate targeting, and inconsistent disbursement schedules. Novelty: This study offers an in-depth identification of supporting and inhibiting factors at the subdistrict level and provides evidence-based recommendations for program optimization. Implications: Enhancing staff competence, regularly updating beneficiary data, improving communication, and ensuring consistent disbursement schedules are crucial for BPNT’s effectiveness in meeting the needs of underprivileged communities. Highlights: Community participation and strategic e-Warong locations support the success of BPNT. The main obstacles include limited human resources, minimal assistance, and inconsistent disbursement schedules. Recommendations focus on improving competence, updating data, and program communication. Keywords: BPNT, Program Implementation, Community Participation, Social Assistance, Poverty Reduction